Design Method for Low Order Two-Degree-of-Freedom Controller Based on Pade Approximation of the Denominator Series Expansion - SUZUKI, Katsuo; ISHIKAWA, Nobuyuki (Journal of the Atomic Energy Society of Japan / Atomic Energy Society of Japan, 1999)
Having advantages of setting independently feedback characteristics such as disturbance rejection specification and reference response characteristics, two-degree-af-freedom (2DOF) control is widely utilized to improve the control performance. The ordinary design method such as model matching usually derives high-ordered feedforward element of 2DOF controller. In this paper, we propose a new design method for low order feedforward element which is based on Pade approximation of the denominator series expansion. The features of the proposed method are as follows: (1) it is suited to realize reference response characteristics in low frequency region, (2) the order of the feedforward element can be setected apart from the feedback element. These are essential to the 2DOF controller design. With this method, 2DOF reactor power controller is designed and its control performance is evaluated by numerical simulation with reactor dynamics model. For this evaluation, it is confirmed that the controller designed by the proposed method possesses equivalent control characteristics to the controller by the ordinary model matching method.